Awareness with Recall in General Anesthesia undergoing Cesarean Section - Gurung, Tara; Shrestha, Sangeeta; Basnet, Ujjwal; Shrestha, Amirbabu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the incidence of awareness with recall in parturient undergoing cesarean section under general anesthesia in Paropakar Maternity and Women’s Hospital. Methods: Retrospective observational cohort study of the patients who underwent cesarean section under general anesthesia from April mid 2014 to April mid 2017 (Baishakh 2071 to Chaitra 2073 BS). Awareness questionnaires filled up through the modified Brice interview. Results: A total of 162 patients underwent Cesarean Section under general anesthesia and138 were included in the study. None of them had awareness and six patients had a dream. Conclusion: No awareness with recall found and prospective study is required to determine the condition.